The Educational Activities of the Roman Catholic Church at the Ukrainian Lands in the Russian Empire in the 19th Century: Problems of Historiography - Inna Shostak (Pedagogical Discourse, 2013)
The article is devoted to the historiography on the educational activities, which involved a white Roman Catholic clergy and monasteries. Particular attention is paid how the parochial school system was studied in literature. Author analyzed the literature and sources on the subject. Overall conservation state of the sources, their informative completeness made it possible to conclude that archival sources are the self-sufficiency for the study of the issue. Analysis of the literature was carried out in problem-chronological order. Pre-revolutionary literature, Ukrainian, Russian and Polish historiography are examined in the article. The author drew attention to the fact that the educational activities of Roman Catholic Church in the Ukrainian lands in the Russian Empire in the 19th century, most papers were considered only in the context of coverage of other issues.